Pembentukan Siswa Moderat-Berkarakter dengan Sosialisasi Moderasi Beragama dan Karakter Anti Bullying di MA Mazro’atul Ulum Lamongan - Afwadzi, Benny; Rifa’i, Ahmad Suzaki; Maskanah, Ulfa; Fadillah, Tegar Adlu; Nuriyah, Addina Silky; Trianingsih, Dini; Al-Farabi, Moh. Rifqi Falah; Zamzami, Muh. Iqbal; Abdullah, Muhammad Yunus; Mubarok, M. Fadliil (INSANIYAH, 2025)
On the one hand, bullying is a very frightening behavior in the world of education. Madrasahs that should be a place to form humanist student characters sometimes become places where bullying occurs. On the other hand, religious moderation is widely voiced as a means to minimize deviant behaviors such as radicalism, terrorism, and even bullying behavior. This community service activity aims to provide a comprehensive and critical understanding through socialization of bullying practices and religious moderation at Madrasah Aliyah Mazro'atul Ulum Paciran Lamongan. The method used in this activity is PAR (Participatory Action Research), which uses observation, documentation, and interviews as data collection techniques. This community service activity can increase understanding and awareness and help people avoid bullying practices in schools and forms of bullying that may not be known. By understanding the types and dangers of bullying for the physical and mental health of victims, a desire arises to create a social environment that is free from bullying practices. In addition, students can understand the nature of religious moderation. The students were also able to link religious moderation as a solution to the bullying actions that occurred. Even so, a long time and cooperation from many parties are needed to make students aware of the negative actions they genuinely do.